Al-Miftāh lil ‘Ulūm: An Alternative Method to Improve the Capability of Students to Read Yellow Books at Al-Anwar Islamic Boarding School, Patereman, Modung, Bangkalan - Eka Sulistiyawati; Anni Annisa'; Indi Aula Jauharoh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islamic boarding schools have a distinctive characteristic, namely the excellence of students in the task of studying the yellow book, a bald book without meaning. The yellow book has become learning literature in Islamic boarding schools and not all students know directly about Arabic grammar. The al-Miftāh lil ‘Ulūm method can help students learn the basics of the yellow book so that they can more quickly understand the rules of nahw and sharraf. This research uses a qualitative method with a case study type of research. The result of this research are that the al-Miftāh lil ‘Ulūm method is a basic practical method for knowing the yellow book, especially learning Arabic grammar for beginners. This method has offered an alternative effort for Al-Anwar students so that it is easier for them to learn the yellow book and interpret it. This method is quite fun because it contains nazham songs and songs about the material and this is method that is not boring.